Fully Automated Production of [68Ga]GaFAPI-46 with Gallium-68 from Cyclotron Using Liquid Targets - Fonseca, Alexandra I. (2023)
68Ga-based radiopharmaceuticals are routinely used for PET imaging of multiple types of tumors. Gallium-68 is commonly obtained from 68Ge/68Ga generators, which are limited in the quantity of activity produced. Alternatively, gallium-68 can easily be produced on a cyclotron using liquid targets. In this study, we optimized the GMP production of [68Ga]GaFAPI-46 using gallium-68 produced via a standard medical cyclotron using liquid targets. Starting from the published synthesis and quality control procedures described for other 68Ga-based radiopharmaceuticals, we have validated the synthesis process and the analytical methods to test the quality parameters of the final product to be used for routine clinical studies. [68Ga]GaFAPI-46 was successfully produced with high radiochemical purity and yield using an IBA Synthera® Extension module. Gallium chloride was produced on a medical cyclotron using a liquid target with activity of 4.31 ± 0.36 GBq at the end of purification (EOP). Analytical methods were established and validated, meeting Ph. Eur. standards. Full GMP production was also validated in three consecutive batches, producing 2.50 ± 0.46 GBq of [68Ga]GaFAPI-46 at the end of synthesis (EOS), with 98.94 ± 0.72% radiochemical purity measured via radio-HPLC. Quality was maintained for up to 3 h after the EOS. Production of [68Ga]GaFAPI-46 was performed and validated using a standard medical cyclotron with liquid targets. The quality control parameters (e.g., sterility, purity, and residual solvents) conformed to Ph. Eur. and a shelf life of 3 h was established. The activity of [68Ga]GaFAPI-46 produced was substantially higher than the one obtained with generators, enabling a better response to the clinical need for this radiopharmaceutical.